Evolution of Modern Insanity Defense: A Critical Review - Ajmal, Ali; Rasool, Faiza; Niazi, Farooq Umair (Annals of Human and Social Sciences, 2023)
The defense of insanity, which is an excuse defense against the criminal liability of a person, went through different phases of evolution before coming to its modern form. During different phases of history, the insanity, and the insanity defense were interpreted differently. The objective of this study is to review the evolution of the defense of insanity employing the doctrinal legal analysis approach. The findings of this review suggest that a critical phase in the evolution of the insanity defense started with the introduction of McNaughton rules. Moreover, different standards of insanity defense such as the Irresistible Impulse Rule, the New Hampshire Product Test, the Durham Rule, the ALI rule, etc. were also introduced. There is still a need for a better standard of insanity defense. The defense of insanity is still evolving and must be studied by adopting multidisciplinary approaches.